Emerging Heterogeneous Supports for Efficient Electrocatalysis. Issue 10 (7th September 2022) - Fan, Meihong; Cui, Lili; He, Xingquan; Zou, Xiaoxin
Abstract: Electrocatalysis plays a fundamental role in many fields, such as metallurgy, medicine, chemical industry, and energy conversion. Anchoring active electrocatalysts with controllable loading and uniform dispersion onto suitable supports has become an attractive topic. This is because the supports can not only have the potential to improve catalytic activity and stability through the interaction between support and catalytic center, but also can reduce precious metal consumption by improving atomic utilization. Herein, recent theoretical and experimental progresses concerning the development of supports to anchor electrocatalytic materials are first reviewed. Next, their controllable syntheses, characterization techniques, metal‐support electronic interactions, and structure‐performance relationships are presented. Some representative carbon supports and non‐carbonaceous supports, as well as recently reported star supports such as 2D supports, single atom catalysts, and self‐supported catalysts are also summarized. In addition, the significant role of support in stabilizing and regulating catalytic active sites is particularly emphasized. Finally, challenges, opportunities, key problems, and further promising solutions for supported catalysts are proposed. Abstract : Supported catalysts have been widely investigated for their flexible structure, abundant component, and efficient catalysis in energy storage and conversion fields. Several representative supported catalysts and electronic metal‐support interactions are reviewed here. Meanwhile, future challenges and opportunities are also discussed.